2009
DOI: 10.1161/circulationaha.108.785949
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and the Interferon-Inducible Chemokine CXCL10 Protect Against Aneurysm Formation and Rupture

Abstract: Background-Vascular disease can manifest as stenotic plaques or ectatic aneurysms, although the mechanisms culminating in these divergent disease manifestations remain poorly understood. T-helper type 1 cytokines, including interferon-␥ and CXCL10, have been strongly implicated in atherosclerotic plaque development. Methods and Results-Here, we specifically examined their role in the formation of abdominal aortic aneurysms in the angiotensin II-induced murine model. Unexpectedly, we found increased suprarenal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 50 publications
9
92
1
1
Order By: Relevance
“…Our results may seem to contradict recent results by King et al (21), who showed that administration of an anti-TGF-β antibody did not alter AAA development in Apoe −/− mice. Unfortunately, the authors presented no data regarding the efficiency of their neutralization protocol.…”
Section: Figurecontrasting
confidence: 99%
“…Our results may seem to contradict recent results by King et al (21), who showed that administration of an anti-TGF-β antibody did not alter AAA development in Apoe −/− mice. Unfortunately, the authors presented no data regarding the efficiency of their neutralization protocol.…”
Section: Figurecontrasting
confidence: 99%
“…Shimizu et al [34] found that IFN-γ receptor-deficient (GRKO) mice had an increased incidence of aneurysm formation and spontaneous rupture, thereby implying the protective role of IFN-γ in aneurysms. Similar to these findings, King et al [35] confirmed the protective role of IFN-γ in aneurysms. They suggested that IFN-γ deficiency (IFN-γ  ) led to increased incidence of AAAs in Ang II treated apolipoprotein E deficient (ApoE  ) mice.…”
Section: Th1 Cellssupporting
confidence: 60%
“…Even this may need to be qualified. While Wang and colleagues concede that another study failed to see worsening of aneurysms in TGFbNAb-treated Ang II-infused mice, they do not comment upon the fact that this study found that TGFbNAb afforded significant protection from Ang II-induced inflammatory aneurysms after Cxcl10 targeting - an event that accentuated aneurysm incidence and severity and death (23). It should also be noted that ARBs or silencing of expression of AT1R have been definitively shown to prevent Ang II-induced aneurysm in rodent models (24)(25)(26)(27)(28).…”
Section: Tgf-β and Models Of Abdominal Aortic Aneurysmmentioning
confidence: 78%